Tool for Rapid Assessment of City Energy (TRACE 2.0) : A Manual for Experts and City Officials - Energy Sector Management Assistance Program (World Bank, Washington, DC, 2018)
TRACE 2.0 incorporates almost 100 recommendations for energy interventions. Following requests from municipal officials for more detailed technical and financial assessment, this version provides simple customizable models for each intervention. Through intervention calculators, users can quickly calculate costs and benefits for each recommendation. The manual is a practical guide for city officials and energy experts. TRACE 2.0 software and manual are available at https://esmap.org/TRACE. ESMAP first developed TRACE in 2008 to help city officials quickly identify energy efficiency performance gaps and opportunities in various public sectors including lighting, water/wastewater, buildings, transportation, solid waste, and power/heating. It guides users through data collection and sector prioritization—considering constraints such as technical capacity and finance—to generate recommendations to improve cities’ energy efficiency. TRACE can help build this framework and initiate a process in a municipal government by using standardized data to address various issues. TRACE has supported more than 80 cities to develop long-term energy efficiency strategies and investment pipelines by increasing understanding of cross-sectoral energy challenges, helping direct funds for dedicated energy efficiency investments, and pointing to legislative adjustments, as well as improving local administrators’ ability to identify, plan, and implement energy efficiency solutions across sectors.